2013
DOI: 10.1021/je400036b
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium at 350 K, Excess Molar Enthalpies at 298 K, and Excess Molar Volumes at 298 K of Binary Mixtures Containing Ethyl Acetate, Butyl Acetate, and 2-Butanol

Abstract: Vapor−liquid equilibrium (VLE), excess molar enthalpies (H E ), and excess molar volumes (V E ) provide means of developing accurate thermodynamic models. In this work, new data of binary mixtures of ethyl acetate, butyl acetate, and 2-butanol are reported. Isothermal VLE data at 350 K were measured by using a circulation still for ethyl acetate + 2-butanol, for 2-butanol + butyl acetate, and for ethyl acetate + butyl acetate. H E was measured at 298 K by using a SETARAM C80 calorimeter equipped with a flow mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 21 publications
(55 reference statements)
3
21
0
Order By: Relevance
“…NPQ kinetics upon exposure to fluctuating light were also monitored in cells treated with DTT, an inhibitor of zeaxanthin biosynthesis. The results in all cases showed that NPQ was largely depleted in the presence of the inhibitor, indicating that its activation is dependent on the xanthophyll cycle in all tested conditions, as expected for this species (Cao et al, 2013;Chukhutsina et al, 2017;Laavi et al, 2013;Park et al, 2019).…”
Section: Role Of Npq In Response To Fluctuating Lightsupporting
confidence: 69%
“…NPQ kinetics upon exposure to fluctuating light were also monitored in cells treated with DTT, an inhibitor of zeaxanthin biosynthesis. The results in all cases showed that NPQ was largely depleted in the presence of the inhibitor, indicating that its activation is dependent on the xanthophyll cycle in all tested conditions, as expected for this species (Cao et al, 2013;Chukhutsina et al, 2017;Laavi et al, 2013;Park et al, 2019).…”
Section: Role Of Npq In Response To Fluctuating Lightsupporting
confidence: 69%
“…Recently, butyl acetate bearing a high ash point (295 K) and a very low freezing point (200 K) has been recognized as a potential biofuel additive. [1][2][3] The low freezing point (200 K) of butyl acetate improves the cold ow properties of biodiesel without signicantly affecting cetane number and the mixture's heat of combustion. Moreover, its high ash point (295 K) makes it safer to use as a biodiesel additive and it also makes it superior to ethyl acetate with a ash point of 269 K and other similar biodiesel additives.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its high ash point (295 K) makes it safer to use as a biodiesel additive and it also makes it superior to ethyl acetate with a ash point of 269 K and other similar biodiesel additives. [1][2][3][4] The process for production of ethyl acetate 5 and butanol 6,7 by renewable routes has been widely researched. Recent advancements in bioprocess and biotechnology has developed an environmentally benign and economically feasible fermentation process to produce butanol and ethyl acetate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations